Great Desire for Extended Life and Health amongst the American Public - Donner, Yoni; Fortney, Kristen; Calimport, Stuart R. G.; Pfleger, Karl; Shah, Munjal; Betts-LaCroix, Joe (Frontiers in Genetics, 2016)
People want to live long, healthy lives. Previous surveys suggest very limited interest in much longer lifespans, but we show that stipulating good health changes responses to favor longer lives by an order of magnitude. Advances in aging research hold out hope for greatly slowed aging with associated good health. Understanding the public's desires correctly is important to avoid misallocation of resources for research.